INVESTIGATING SELF-REGULATED LEARNING STRATEGIES FOR DIGITAL LEARNING RELEVANCY (Malaysian Journal of Learning and Instruction, 2021)
Purpose: The rise of digital learning and the prevalence of affordable devices are convenient for young adults who are accustomed to using their digital devices for almost everything such as communication, collaboration, and accessing multiple sources of information for solutions. However, the lack of ability to self-regulate learning processes has led to poor learning performance among undergraduates. Therefore, this study examined the effects of self-regulated learning strategies (SRLS) on learning performance among Malaysian IT undergraduates.Methodology: A sample of IT undergraduates from private higher education institutions in Malaysia participated in the study. Quantitative data from a total of 563 respondents was collected through questionnaire surveys and analysed using PLS-SEM. The common method variance was utilized in this paper. Findings: The findings of this study constitute essential results that three out of four SRLS domains (cognitive engagement, resource management, and motivational beliefs) positively influenced the students’ perception of learning performance. Significance: This study provides insight into the best SRLS to excel in digital learning for deeper learning particularly in the Malaysian context. Implications of the findings on higher education institutions as well as recommendations for future research are discussed.